Hypercapnic ventilatory response in epilepsy patients treated with VNS: A case‐control study. (15th July 2021) - Sainju, Rup K.; Dragon, Deidre N.; Winnike, Harold B.; Ten Eyck, Patrick; Granner, Mark A.; Gehlbach, Brian K.; Richerson, George B.
Abstract: Objective: Central CO2 chemoreception (CCR), a major chemical drive for breathing, can be quantified with a CO2 re‐breathing test to measure the hypercapnic ventilatory response (HCVR). An attenuated HCVR correlates with the severity of respiratory dysfunction after generalized convulsive seizures and is a potential biomarker for sudden unexpected death in epilepsy (SUDEP) risk. Vagus nerve stimulation (VNS) may reduce SUDEP risk, but for unclear reasons the risk remains higher during the first 2 years after implantation. The vagus nerve has widespread connections in the brainstem, including key areas related to CCR. Here we examined whether chronic electrical stimulation of the vagus nerve induces changes in CCR. Methods: We compared the HCVR in epilepsy patients with or without an active VNS in a sex‐ and age‐matched case‐control study. Eligible subjects were selected from a cohort of patients who previously underwent HCVR testing. The HCVR slope, change in minute ventilation (VE) with respect to change in end tidal (ET) CO2 (∆ VE/ ∆ ETCO2) during the test was calculated for each subject. Key variables were compared between the two groups. Univariate and multivariate analyses were carried out for HCVR slope as dependent variable. Results: A total of 86 subjects were in the study. HCVR slope was significantly lower in the cases compared to the controls. Cases had longer duration of epilepsy and higher number of anti‐epileptic drugs (AEDs) tried during lifetime. Having active VNS and ETCO2 were associated with a low HCVR slope while high BMI was associated with high HCVR slope in both univariate and multivariate analyses. Discussion: We found having an active VNS was associated with relatively attenuated HCVR slope. Although duration of epilepsy and number of AEDs tried during lifetime was significantly different between the groups, they were not predictors of HCVR slope in subsequent analysis. Conclusion: Chronic electrical stimulation of the vagus nerve by VNS may be associated with an attenuated CCR [Correction added on 24 November 2021, after first online publication: The preceding sentence has been revised from "Chronic electrical stimulation of VNS nerve by VNS…"]. A larger prospective study may help to establish the time course of this effect in relation to the time of VNS implantation, whether there is a causal relationship, and determine how it affects SUDEP risk.